Cinderella - Brooks, Felicity; Allen, Francesca; Litchfield, Jo (London : Usborne, 2008)
An illustrated retelling of the classic story of Cinderella.
On board pages, with die-cut page tabs.
3.3
K-3.
K-3
Keywords: Cinderella (Legendary character); Fairy tales; Cinderella (Legendary character); Fairy tales; Cinderella (Legendary character); Fairy tales